(untitled) (International Journal of Engineering and Computer Science, 2015)
Global system for mobile communication has changed the face of communication and information exchange, much as the internet did with the advances made in the mobile technology arena, new opportunities are created. Mobile communication (m-commerce) is one such opportunity. Each new advance in technology brings with its associated risks. This paper focuses on the risks involved with m-commerce for the business industry. This paper provides a detailed overview of basic service that any m-commerce application should provide to the business industry. These principles provide the foundation for securing any financial transaction over untrusted Networks. The security of GSM networks has come under attack in the past. This is largely due to the fact that the GSM consortium opted to develop their security technologies in secret, rather than in public domain. This paper aims to evaluate the security offered by GSM and access potential attacks in order to further understand risks associated with m-commerce business over GSM. Keywords m-commerce, GSM, E-commerce, customer, receive order, invoice, shopping goods.